Efeitos da recessão econômica sobre a situação de pobreza no Brasil - Matias, Débora Ferreira (2021)
This research aims to analyze the effects of the Brazilian economic recession from the second quarter of 2014 to the fourth quarter of 2016 on the situation of poverty in Brazil and to determine which individual characteristics are most associated with the state of vulnerability. It composes a poverty profile based on the micro database of the Continuous National Household Sample Survey (Continuous PNAD), available between 2012 and 2019. For this work, the poverty line was that recommended by The World Bank, which defines poverty as families with per capita income below US$ 5.50 per day in terms of Purchasing Parity Power (PPP). The estimation of poverty indicators is carried out by the indicators proposed by Foster, Greer and Thorbecke (1984). The logistic regression model was utilized using the maximum likelihood technique. The results showed that poverty rates were higher for residents in the Northeast and North regions, as well as among residents in rural areas. Regarding the demographic profile, there were higher rates of poverty in younger age groups and among people who declared themselves black or mixed race. There were no major differences between men and women. Regarding the level of schooling, the highest poverty rate was observed among people with a lower level of formal education.